The determinants of Bank Cost Inefficiency in ASEAN Banking - Izah Mohd Tahir,; Abdul Mongid,; Sudin Haron, (Penerbit Universiti Kebangsaan Malaysia, 2012)
This study examines the determinants of cost inefficiency of banks operating in 6 member countries of the Association of Southeast Asian Nations (ASEAN): Indonesia, Malaysia, Singapore, Thailand, the Philippines, and Vietnam. First, we estimate the cost inefficiency using the Stochastic Frontier Analysis. Second, we regress the estimated cost inefficiencies on a set of bank specific variables (size, equity to total asset, loan to total asset, personnel expenses to total expenses) and environmental variables (corruption, economic growth and economic freedom) using a Tobit regression analysis. We use a panel dataset of 625 banks in the ASEAN countries for the period from 2003 to 2008. Our results show that the average cost inefficiency during the period is about 33% of the observed total costs. Banks in Singapore exhibit the lowest cost inefficiency relative to banks in the other ASEAN countries. Our second stage results suggest that bank specific variables and economic growth are important determinants of bank cost inefficiencies in ASEAN banking. The impact of corruption and economic freedom is also evident, but only to a limited extent.